2005
DOI: 10.1258/0049475053001976
|View full text |Cite
|
Sign up to set email alerts
|

Isolated splenic tuberculosis

Abstract: Tuberculosis isolated to the spleen is a rare clinical entity particularly in the non-HIV-positive patient population. In the four patients described, two presented with thrombocytopenia; in two patients the condition was diagnosed serendipitously at laparotomy undertaken for abdominal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 11 publications
0
24
1
Order By: Relevance
“…Isolated splenic TB, as we present here, is a rare form of extrapulmonary TB. Although Winternitz (1912) categorised splenic TB as a primary and secondary form, some scholars opine that all patients of splenic TB are secondary to the previous infection of tubercle bacilli in other organs 2. Spleen is the third most common organ affected in miliary TB, following the lung and liver, especially in immunocompromised patients 3.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated splenic TB, as we present here, is a rare form of extrapulmonary TB. Although Winternitz (1912) categorised splenic TB as a primary and secondary form, some scholars opine that all patients of splenic TB are secondary to the previous infection of tubercle bacilli in other organs 2. Spleen is the third most common organ affected in miliary TB, following the lung and liver, especially in immunocompromised patients 3.…”
Section: Discussionmentioning
confidence: 99%
“…Although Winternitz (1912) categorized splenic TB as a primary or secondary form, some scholars insist that all patients with splenic TB are secondary to the previous infection of tubercle bacillus in other organs. 7 In our cases, the patient denied a history of TB and there was no indication of any other involvement in other sites or organs at the time of admission. There are no specific symptoms for establishing the diagnosis of splenic TB.…”
Section: Discussionmentioning
confidence: 55%
“…In Iran, one case was reported in 2002 [9]. Adil A et al reported ten immunocompetent individuals [10], while Singh et al reported four cases [11] with isolated primary splenic tuberculosis.…”
Section: Discussionmentioning
confidence: 99%